Substitution of surgical care within benign gynaecology during COVID-19: waste of a good crisis? – a quantitative longitudinal study in the Netherlands - Xander Koolman; Wouter J K Hehenkamp; Robert A de Leeuw; Eva L M Velthuijs; Ismail Ismail (BMJ Open)
Objective To examine the impact of the COVID-19 pandemic on the substitution of surgical procedures in benign gynaecology in the Netherlands.Design Quantitative longitudinal study evaluating the effects of the COVID-19 pandemic.Setting Nationwide healthcare delivery was analysed across six benign gynaecological pathways from 2016 to 2022 using Vektis and Dutch Hospital Data (DHD), accessed via Statistics Netherlands (Centraal Bureau voor de Statistiek).Participants The study focused on six benign gynaecological pathways classified using Dutch Diagnosis Treatment Combinations (DTCs): heavy menstrual blood loss (G11), uterine fibroids (G15), endometriosis (G17), prolapse (G25), infertility treatment (F11) and first trimester pregnancy complications (Z12). All patients receiving care within these pathways between 1 January 2016 and 31 December 2022 were included. Exclusions applied to all patients under 18 years old and, only within the menstrual disorder pathway, patients over 51 years old to exclude most postmenopausal blood loss cases where no alternative treatment applies.Interventions Cohorts from the initial pandemic year (2020) were compared with four prepandemic cohorts (2016–2019) and late-pandemic (2021) and postpandemic (2022) cohorts.Primary and secondary outcome measures The primary outcome was the trend in the total number of patients in surgical and non-surgical procedure groups across cohort periods. Secondary outcomes included trends within individual pathways.Results The analysis identified a significant reduction in benign gynaecological care during 2020, with an 18.3% (p<0.001) decrease in surgical procedures and a 6% (p=0.02) decrease in non-surgical procedures across all pathways. During the COVID-19 pandemic, surgical care showed the largest significant declines in infertility treatment (−19.3%, p<0.001) and prolapse and heavy menstrual bleeding (both −17.5%, p<0.001), while non-surgical care decreased less markedly, with the largest significant drop in prolapse care (−10.4%, p=0.001). Non-surgical procedures generally returned to pre-pandemic levels, whereas surgical care remained reduced. These differences were conducted using regression models that adjusted for time trends and the COVID-19-related impact.Conclusions The COVID-19 pandemic significantly disrupted both surgical and non-surgical procedures within benign gynaecological pathways. Reduced care uptake during the pandemic waves was not recovered but instead forgone. The reduction in surgical procedures did not correspond with increased use of non-surgical alternatives. Future research should prioritise evaluating the long-term impacts of this disruption on patients and society.